Total body irradiation plus fludarabine versus thiotepa, busulfan plus fludarabine as a myeloablative conditioning for adults with acute lymphoblastic leukemia treated with haploidentical hematopoietic cell transplantation. A study by the Acute Leukemia Working Party of the EBMT - Swoboda, Ryszard; Labopin, Myriam; Giebel, Sebastian; Angelucci, Emanuele; Arat, Mutlu; Aljurf, Mahmoud; Sica, Simona; Pavlu, Jiri; Socié, Gerard; Bernasconi, Paolo; Rigacci, Luigi; Tischer, Johanna; et al. (Bone marrow transplantation, 2022)
Optimal conditioning for adults with acute lymphoblastic leukemia (ALL) treated with haploidentical hematopoietic cell transplantation (haplo-HCT) and post-transplant cyclophosphamide has not been established so far. We retrospectively compared outcomes for two myeloablative regimens: fludarabine + total body irradiation (Flu-TBI, n = 117) and thiotepa + iv. busulfan + fludarabine (TBF, n = 119). Patients transplanted either in complete remission (CR) or with active disease were included in the analysis. The characteristics of both groups were comparable except for patients treated with TBF were older. In univariate analysis the incidence of non-relapse mortality (NRM) at 2 years was increased for TBF compared to Flu-TBI (31% vs. 19.5%, p = 0.03). There was a tendency towards reduced incidence of relapse after TBF (p = 0.11). Results of multivariate analysis confirmed a reduced risk of NRM using Flu-TBI (HR = 0.49, p = 0.03). In the analysis restricted to patients treated in CR1 or CR2, the use of Flu-TBI was associated with a decreased risk of NRM (HR = 0.34, p = 0.009) but an increased risk of relapse (HR = 2.59, p = 0.01) without significant effect on survival and graft-versus-host disease. We conclude that for haplo-HCT recipients with ALL, Flu-TBI may be preferable for individuals at high risk of NRM while TBF should be considered in cases at high risk of relapse.
Keywords: Vidarabine; nemoc štěpu proti hostiteli; akutní myeloidní leukemie; Busulfan; příprava pacienta k transplantaci; Retrospective Studies; Transplantation Conditioning; Recurrence; retrospektivní studie; Humans; Leukemia, Myeloid, Acute; dospělí; transplantace hematopoetických kmenových buněk; Whole-Body Irradiation; thiotepa; Hematopoietic Stem Cell Transplantation; lidé; celotělové ozáření; vidarabin; akutní lymfatická leukemie; Graft vs Host Disease; Thiotepa; busulfan; recidiva; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Adult